Shadows Over Arbitration - Woods, H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
The author presents what he believes to be an excessive dose of public intervention in the relationship between labour and management and more particularly in the field of arbitration.